Educational And Mentoring Activities Through An Emergency School Program For Flood-Affected Children In Beuringen Village, Meurah Dua Subdistrict, Pidie Jaya: Edukasi dan Pendampingan Sekolah Darurat Bagi Anak Korban Bencana Banjir Di Desa Beuringen, Kecamatan Meurah Dua Pidie Jaya - Dwi Putri Rejeki; Asridiana; Fita Nelyza; Irma Zarwinda; Eva Novita (Akademi Farmasi YPPM Mandiri, 2026)
This community service activity aims to provide educational support and mentoring through an emergency school program for children affected by flood disasters in Beuringen Village, Meurah Dua Subdistrict, Pidie Jaya Regency. Flood disasters have disrupted educational processes and negatively impacted children’s psychosocial conditions, thus requiring alternative efforts to ensure the continuity of learning in emergencies. The implementation method consisted of three stages: planning, implementation, and evaluation. The activities were carried out directly (offline) by a community service team in collaboration with Bimbel Aswaja Pidie Jaya. The program included basic learning activities such as reading and writing, homework assistance, hygiene education, interactive learning activities, and the distribution of aid to participants. The evaluation was conducted through observation and a simple emoticon-based instrument to measure children’s happiness responses. The results indicate that the emergency school program was successfully implemented and received positive responses from participants. Approximately 85% of the children expressed happy to very happy responses toward the activities. The program not only improved learning motivation but also contributed positively to the psychosocial recovery of children after the disaster. In conclusion, the emergency school program can serve as an effective alternative solution to maintain the continuity of children’s education while supporting psychosocial recovery in disaster-affected areas.